Meta Analisis Hasil Penelitian Model-Model Rehabilitasi Narkoba oleh Lembaga Pemerintah, Masyarakat dan Pesantren di Jabodetabek - Ismet Firdaus (Social Welfare Study Program, 2015)
The rehabilitation victims of drug abuse in Indonesia is not only done by government agencies, but also by NGOs and Pesantren. With this type of study, meta-analysis of 15 analytical research report, the results illustrated that in government agencies and non-governmental organizations, program therapeutif community (TC) becomes an important part in the Social Rehabilitation to clients of drug abusers, with the support of family and interaction among clients/patients harmony in social rehabilitation program is an important factor for the improvement or cure the patient/client victims of drug abuse. Detoxification (expenditure toxins drugs to patients/clients) that exist in government agencies and NGOs about the same, while in boarding school detoxification is different, for example by drinking water prayer. Meanwhile, the rehabilitation program in Islamic schools put more emphasis on improving the client’s relationship with God through the practice of worship ritual which he believed to be implicated in healing drug abusers clients.Keywords: Meta analisis, Rehabilitasi Medis, Rehabilitasi Sosial, Theraputif Community dan Narkoba.